Trends in incidence, mortality and disability-adjusted life years of colorectal cancer in East Asia (1990–2021): An analysis of the Global Burden of Disease study 2021 - Yuanyi Cao; Liyuan Yang; Luhan Fan; Xinyao Liu; Chao Yang; Zhengxing Xu; Qingbi Zhang; Junhui Zhang (PLoS ONE, 2025)
Background Colorectal cancer (CRC) poses a significant health challenge in East Asia. This study examined long-term trends in CRC incidence, mortality and disability-adjusted life years (DALYs) and their key drivers across five East Asian countries (China, Japan, South Korea, North Korea and Mongolia) from 1990–2021. Methods Using Global Burden of Disease Study 2021 data, we assessed temporal trends using joinpoint regression, age/period/birth cohort effects through age-period-cohort analysis, and key drivers via decomposition analysis; we also evaluated associations between CRC burden and the Socio-Demographic Index (SDI). Results Between 1990 and 2021, descriptive analysis showed CRC age-standardised incidence rates (ASIRs) increased in all East Asian countries, while age-standardised mortality rates (ASMRs) and age-standardised DALY rates (ASDRs) generally declined, although 95% uncertainty intervals (UIs) overlapped in some countries. Joinpoint regression revealed overall increasing ASIR trends, with South Korea showing the largest average annual percentage changes (AAPCs) (males 2.18%, females 1.41%). ASMRs and ASDRs generally decreased, particularly among females; however, Mongolian males experienced slight increases (ASMR AAPC = 0.50%; ASDR AAPC = 0.44%). Relative risks for CRC incidence, mortality and DALYs increased with age, peaking in older groups. Period effects increased approximately linearly, while cohort effects decreased for younger generations. Decomposition analysis showed ageing and population growth were the main contributors to increased CRC burden. SDI showed an overall positive association with CRC burden, with heterogeneity by country and sex. Conclusions Joinpoint analysis (1990–2021) demonstrated increases in CRC incidence (predominantly males) and declines in mortality/DALY rates (especially females) across most East Asian countries; however, substantial changes (non-overlapping UIs) were limited to few groups, warranting cautious interpretation. Despite progress, the persistent overall burden remains substantial, mainly driven by ageing and population growth. These findings underscore the need for country- and sex-specific prevention, screening, and lifestyle strategies.